2017
DOI: 10.2306/scienceasia1513-1874.2017.43.155
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Sorghum bicolor antioxidant activity on harvest time

Abstract: ABSTRACT:This study was done to examine the correlation between differential contents of antioxidants and their antioxidative activities in the seeds obtained from two sorghum cultivars (Nampungchal and Hwanggeumchal) according to harvest time post heading, and to understand the properties of the harvested seeds. The seeds were harvested every 5 days from 25-55 days post heading. Length, width, thickness, and morphological properties of the obtained seeds were increased in proportion to the harvest time. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Moreover, Jeon et al [ 81 ] observed variations in the phenolic compounds and antioxidant properties owing to differences in the harvesting time of sorghum genotypes. In another study, the irradiance period of the growing sorghum genotypes influenced the phenolic content and antioxidant activity of sorghum plants [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Jeon et al [ 81 ] observed variations in the phenolic compounds and antioxidant properties owing to differences in the harvesting time of sorghum genotypes. In another study, the irradiance period of the growing sorghum genotypes influenced the phenolic content and antioxidant activity of sorghum plants [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity in sorghum grains is related to the phenolic compound content, from which tannins, phenolic acids, and flavonoids are the main reasons for its capacity to scavenge oxidative radicals (Afiyi et al., 2012). Antioxidant activity is lower in white sorghum grains than in the dark testa varieties, and differences have been found between varieties with a similar color of testa at different harvest times(Jeon et al., 2017; Shen et al., 2018; Wu et al., 2017). Antioxidant activity values in white sorghum grains ranging from 340 to 500 µM TE /g have been reported but stress conditions during agronomic production can lead to a sharp increase doubling these values (Wu et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa penelitian lain melaporkan hal yang serupa, perbedaan umur panen memengaruhi aktivitas antioksidan pada biji borage dan biji Aesculum hippocastanum (Mhamdi et al, 2010;Kedzierski et al, 2016). Jeon et al (2017) melaporkan aktivitas antioksidan pada biji sorghum mengalami penurunan mulai dari umur panen 25 hingga 55 hari. Penurunan aktivitas antioksidan pada sorghum ini berkolerasi dengan terjadinya penurunan kandungan total fenol, total flavonoid dan tanin pada biji sorgum.…”
Section: Aktivitas Antioksidanunclassified